Arts and Crafts Based knowledge from Arctic - Huhmarniemi, Maria; Jónsdóttir, Ásthildur (2020)
Sustainable development was the key theme of the Arctic Arts Summit 2019, and issues of sustainable development were pondered in many presentation, panel discussions and artworks in the exhibitions. One thread to the theme was handmade – design and contemporary art based on traditions, folklore and crafts. In this presentation we evaluate an exhibition project produced as part of the Summit. We ponder what kind of knowledge contemporary are can pass from the Arctic traditions and discuss Arctic knowledge in between Indigenous and non-Indigenous cultures as well as so called colonialization of mind. The presentation is based on the Fringe exhibition that was shown in the Arctic Arts Summit 2019 in Rovaniemi. The title of the exhibition Fringe refers to the outer edge, the margin or the periphery. When something is regarded as peripheral, marginal or extreme, it often needs to be respected and protected. The exhibition made connections through art and crafts, showing works by artists who have studied the theme and practice of dialogue from various perspectives with handmade techniques. The collaboration aimed to shed light on cultural awareness and promote rich Arctic dialogue. We aimed to both create new knowledge and research it through artistic work as well as to present the knowledge to decisions makers and other participants of the Summit. While there is an ongoing need to bridge the gaps between science, Indigenous Knowledge, policy making and other forms of decision making to communication and knowledge-based development in the Arctic, the exhibition project was one effort to respond the need. In this presentation we evaluate the results of the project.